Emergence of Financial Intermediaries in Electronic Markets: The Case of Online P2P Lending - Sven C. Berger; Fabian Gleisner (BuR - Business Research, 2009)
We analyze the role of intermediaries in electronic markets using detailed data of more than 14,000 originated loans on an electronic P2P (peer-to-peer) lending platform. In such an electronic credit market, lenders bid to supply a private loan. Screening of potential borrowers and the monitoring of loan repayment can be delegated to designated group leaders. We find that these market participants act as financial intermediaries and significantly improve borrowers' credit conditions by reducing information asymmetries, predominantly for borrowers with less attractive risk characteristics. Our findings may be surprising given the replacement of a bank by an electronic marketplace.
urn:nbn:de:0009-20-19400
Keywords: 650; asymmetric information; electronic markets; intermediation; social lending; Finanzintermediation; Asymmetrische Information; Social Web; Kreditgeschäft; E-Business